A high entropy carbide ceramic material and its preparation method and application
Through a two-step rapid sintering method, including carbon thermal reduction and electric field sintering, the problems of small component space, uneven distribution of metal elements, and high oxide impurities in the preparation of existing high-entropy carbide ceramic materials were solved, and the preparation of high-density and high hardness of high-entropy carbide ceramic materials was achieved, which expanded its application prospects.
Patent Information
- Application Number
- CN202311002492.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-08-09
AI Technical Summary
The existing rapid sintering method of high-entropy carbide ceramics has the problems of small space for preparing sample components, uneven distribution of metal elements, and high oxide impurities, which limits its application prospects.
A two-step rapid sintering method is adopted, first mixing the metal oxide powder with the carbon powder for a carbon thermal reduction reaction to form a clinker powder, and then using the electric field sintering method in a protective atmosphere to prepare high-entropy carbide ceramic materials.
It has achieved the preparation of high-density and high hardness of high entropy carbide ceramic materials, with large component space, uniform distribution of metal elements, and no oxide impurity phases, which are suitable for industrial production and widespread applications.
Smart Images

Figure CN117164361B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high entropy ceramics, and in particular to a high entropy carbide ceramic material and a preparation method and application thereof. Background Art
[0002] High entropy carbides have the characteristics of high melting point, high hardness, low thermal conductivity, excellent corrosion resistance, and excellent catalytic performance, showing attractive application prospects in the fields of aerospace, high-end cutting tools, nuclear power, microelectronics, etc. At present, the preparation methods of high entropy carbide ceramics mainly include pressureless sintering, hot pressing sintering, spark plasma sintering, rapid sintering, etc., and the rapid sintering method is conducive to the component screening and performance regulation of high entropy carbides due to its advantages of high timeliness and low energy consumption, and has a broader application prospect. The document "Ultrafast high-temperature synthesis and densification of high-entropy carbides, Hai-Rong Mao, Er-Ting Dong, Shen-BaoJin, Xiao-Ming Qiu, Ping Shen. Journal of the European Ceramic Society, 2022(42): 4053-4065" discloses a rapid sintering method for high-entropy carbide ceramics. This method can prepare 8-element high-entropy carbide ceramics at most, and the density of the ceramics can reach 98.5%. However, there are problems such as the small component space of the prepared samples (only eight or less components), uneven distribution of metal elements, and high content of oxide impurities (introduced by ball milling), which greatly limits its application.
[0003] Therefore, it is of great significance to develop a rapid sintering method for high-entropy carbide ceramics and to prepare high-entropy carbide ceramics with huge component space, uniform distribution of metal elements, and low oxide impurity content. Summary of the invention
[0004] The purpose of the present invention is to provide a high entropy carbide ceramic material and a preparation method and application thereof.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing a high entropy carbide ceramic material comprises the following steps:
[0007] 1) mixing and grinding metal oxide powder and carbon powder, wherein the metal oxide powder consists of at least six of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder, to obtain a mixed powder;
[0008] 2) Pressing the mixed powder into a green body, then covering the upper and lower surfaces of the green body with graphite paper coated with hexagonal boron nitride on the upper surface and then embedding graphite felt, then placing it in a protective atmosphere and electrifying the graphite felt to cause the green body to undergo a carbon thermal reduction reaction, then taking out the obtained clinker, grinding and sieving it to obtain clinker powder;
[0009] 3) The clinker powder is pressed into a clinker body, and then the clinker body is wrapped with graphite paper coated with hexagonal boron nitride and embedded with graphite felt, and then the graphite felt is electrified in a protective atmosphere to perform electric field sintering on the clinker body, thereby obtaining a high entropy carbide ceramic material.
[0010] Preferably, in step 1), the ratio of the total molar amount of metal atoms in the metal oxide powder to the molar amount of carbon powder is 1:1.
[0011] Preferably, the metal oxide powder in step 1) is composed of at least six of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder in equal molar ratios of metal elements.
[0012] Preferably, in step 1), the particle sizes of the HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder are all 1 μm to 3 μm, and the purity is ≥99.9%.
[0013] Preferably, the particle size of the carbon powder in step 1) is ≤ 2 μm and the purity is ≥ 99.95%.
[0014] Preferably, the pressing in step 2) is carried out at a pressure of 8 MPa to 10 MPa, and the holding time is 1 min to 3 min.
[0015] Preferably, the green body in step 2) is in the form of a disc with a diameter of ≤16 mm and a thickness of ≤3.5 mm. The upper and lower surfaces of the green body are covered with graphite paper coated with hexagonal boron nitride to prevent the green body from reacting with the graphite paper and the graphite felt.
[0016] Preferably, the size of the graphite felt in step 2) is 100 mm to 120 mm in length, 15 mm to 20 mm in width, and 4.75 mm in thickness.
[0017] Preferably, the protective atmosphere in step 2) is an argon atmosphere.
[0018] Preferably, the carbon thermal reduction reaction in step 2) is specifically performed as follows: connecting the two ends of the graphite felt to an alternating current, increasing the current from 0 to 80A to 85A at a rate of 2A / s to 4A / s, and then maintaining for 55s to 65s. The carbon thermal reduction reaction can cause the metal oxide to completely react to form a high entropy primary phase and other solid solution secondary phases, which can ensure that the high entropy carbide ceramic material does not contain an oxide impurity phase, and can ensure that a high-density high entropy carbide ceramic material is obtained.
[0019] Preferably, the sieve used in step 2) is a 100-mesh nylon sieve.
[0020] Preferably, the pressing in step 3) is carried out at a pressure of 6 MPa to 8 MPa, and the holding time is 1 min to 3 min.
[0021] Preferably, the clinker blank in step 3) is in the form of a disc with a diameter of ≤10 mm and a thickness of ≤2 mm. The clinker blank is coated with graphite paper coated with hexagonal boron nitride to prevent the clinker blank from reacting with the graphite paper and graphite felt, thereby preventing the surface of the high entropy carbide ceramic material from being eroded by carbon and deformed.
[0022] Preferably, the size of the graphite felt in step 3) is 100 mm to 120 mm in length, 15 mm to 20 mm in width, and 4.75 mm in thickness.
[0023] Preferably, the protective atmosphere in step 3) is an argon atmosphere.
[0024] Preferably, the specific operation of the electric field sintering in step 3) is: connect the two ends of the graphite felt to alternating current, then increase the current from 0 to 4A~6A within 5s~10s, and then maintain for 10s~15s, then increase the current to 30A~40A within 5s~10s, and then maintain for 10s~15s, then increase the current to 55A~60A within 5s~10s, and then maintain for 30s~35s, and then turn off the power for cooling.
[0025] A high entropy carbide ceramic material is made by the above preparation method.
[0026] An application of the high entropy carbide ceramic material as described above in preparing tool coatings, bearing coatings, bulletproof vest protective layers or tank armored vehicle bulletproof layers.
[0027] The beneficial effects of the present invention are as follows: the high entropy carbide ceramic material of the present invention has the advantages of large component space, high density, no oxide impurity phase, excellent mechanical properties, etc., and its preparation method has the advantages of simple operation, extremely short reaction time, low equipment requirements, simple process flow, low synthesis cost, low energy consumption, etc., is suitable for component screening and large-scale industrial production, and has broad application prospects.
[0028] Specifically:
[0029] 1) The present invention uses cheap transition metal oxide powder and carbon powder as raw materials, and prepares high entropy carbide ceramic materials with any six or more elements of Hf, Zr, Ti, Ta, Nb, Cr, Mo, V and W by a two-step rapid sintering method, thereby overcoming the difficulty that the traditional one-step rapid sintering method cannot quickly prepare high entropy carbide ceramics with larger component space, uniform distribution of metal elements and no oxide impurity phase;
[0030] 2) The high entropy carbide ceramic material of the present invention has a high density (92.0% to 95.5%), and its mechanical properties can be optimized through component design (from six elements to nine elements, the hardness is increased from 25.6GPa to 29.6GPa). Due to its ultra-high hardness, it can be used to make high-end tool coatings, bearing coatings, bulletproof vest protective layers, tank armored vehicle bulletproof layers, etc., and has broad application prospects in the fields of cutting tools, injection molding, mining drill bits, military armor, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : This is the XRD diagram of the clinker powder in Examples 1 to 3.
[0032] Figure 2 1 is the XRD diagram of the high entropy carbide ceramic material of Examples 1 to 3.
[0033] Figure 3 The SEM image and EDS element surface distribution map of the high entropy carbide ceramic material of Example 3.
[0034] Figure 4 1 to 4 are XRD diagrams of the high entropy carbide ceramic materials of Comparative Examples 1 to 4. DETAILED DESCRIPTION
[0035] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0036] The particle sizes of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder in Examples 1 to 3 and Comparative Examples 1 to 4 are all 1 μm to 3 μm, and the purity is all ≥99.9%.
[0037] The particle size of the carbon powder in Examples 1 to 3 and Comparative Examples 1 to 4 is ≤ 2 μm, and the purity is ≥ 99.95%.
[0038] Embodiment 1:
[0039] A high entropy carbide ceramic material, the preparation method of which comprises the following steps:
[0040] 1) Add 0.35 g of HfO2 powder, 0.21 g of ZrO2 powder, 0.37 g of Ta2O5 powder, 0.22 g of Nb2O5 powder, 0.13 g of TiO2 powder, 0.13 g of Cr2O3 powder and 0.37 g of carbon powder into an agate mortar and grind manually for 60 min to obtain a mixed powder;
[0041] 2) 1.2 g of the mixed powder was placed in a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 8 MPa, and the pressure was maintained for 1 min to obtain a green body (thickness of about 3 mm);
[0042] 3) A through hole of about 20 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 100 mm in length, 16 mm in width and 4.75 mm in thickness. Then, the upper and lower surfaces of the green body were covered with graphite paper coated with hexagonal boron nitride of the same size and then inserted into the through hole of the graphite felt. Then, the electrodes were clamped at both ends of the graphite felt along the length direction and then suspended in the reactor cavity. The reactor was closed and the reactor cavity was first evacuated with a mechanical pump to make the vacuum pressure count value reach 10 Pa. Then, the molecular pump was turned on to continue the evacuation process until the vacuum pressure count value was less than 8×10 - 3 Pa, then slowly introduce argon to normal pressure, turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 80A at a rate of 2A / s, and then keep it for 55s, turn off the power switch and cool it naturally, then take out the obtained clinker, grind it and pass it through a 100-mesh nylon sieve, take the powder under the sieve, and obtain clinker powder (recorded as 6HEC-S1);
[0043] 4) 0.5 g of clinker powder was placed in a mold (the mold cavity was cylindrical with a diameter of 10 mm), and the pressure was slowly increased to 6 MPa, and the pressure was maintained for 1 min to obtain a clinker body (thickness of about 1.5 mm);
[0044] 5) A through hole of about 20 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 100 mm in length, 16 mm in width and 4.75 mm in thickness, and then a graphite paper coated with hexagonal boron nitride was folded in half to form a carrier with a length of 20 mm and a width of 15 mm. The clinker blank was then inserted into the carrier (the upper and lower surfaces of the clinker blank were not completely in contact with the graphite paper), and then inserted into the through hole of the graphite felt. Then, the electrodes were clamped at both ends of the graphite felt along the length direction, and then suspended in the reactor cavity. The reactor was closed, and the reactor cavity was first vacuumed with a mechanical pump to make the vacuum pressure count value reach 10 Pa, and then the molecular pump was turned on to continue the vacuuming process until the vacuum pressure count value was less than 8×10 -3Pa, and then slowly introduce argon to normal pressure, then turn on the power switch to connect the two ends of the graphite felt to AC, then increase the current from 0 to 4A within 5s, and then keep it for 10s, then increase the current to 30A within 5s, and then keep it for 10s, then increase the current to 55A within 5s, and then keep it for 30s, then turn off the power and cool it to room temperature, and then you can get a high entropy carbide ceramic material (six-element high entropy carbide (Hf 1 / 6 Zr 1 / 6 Ta 1 / 6 Nb 1 / 6Ti 1 / 6 Cr 1 / 6 )C, denoted as 6HEC).
[0045] Performance Test:
[0046] The X-ray diffraction (XRD) pattern of the clinker powder in this embodiment is as follows: Figure 1 As shown, the XRD pattern of the high entropy carbide ceramic material of this embodiment is as follows Figure 2 shown.
[0047] Depend on Figure 1 It can be seen that the clinker powder 6HEC-S1 in this embodiment contains a high entropy main phase and other solid solution secondary phases.
[0048] Depend on Figure 2 It can be seen that the high entropy carbide ceramic material 6HEC in this embodiment is a pure phase and does not contain other impurity phases.
[0049] After testing (the testing method is the same as that of Example 3), the six constituent elements Hf, Zr, Ta, Nb, Ti and Cr in the high entropy carbide ceramic material 6HEC of this embodiment are evenly distributed without obvious segregation, the density of 6HEC is 95.5%, and the hardness value of 6HEC under a load of 0.49N is 25.6GPa.
[0050] Embodiment 2:
[0051] A high entropy carbide ceramic material, the preparation method of which comprises the following steps:
[0052] 1) Add 0.39 g of HfO2 powder, 0.23 g of ZrO2 powder, 0.41 g of Ta2O5 powder, 0.25 g of Nb2O5 powder, 0.15 g of TiO2 powder, 0.14 g of Cr2O3 powder, 0.27 g of MoO3 powder and 0.50 g of carbon powder into an agate mortar and grind manually for 60 min to obtain a mixed powder;
[0053] 2) 1.2 g of the mixed powder was placed in a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 9 MPa, and the pressure was maintained for 2 min to obtain a green body (thickness of about 3 mm);
[0054] 3) A through hole of about 20 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 100 mm in length, 16 mm in width and 4.75 mm in thickness. Then, the upper and lower surfaces of the green body were covered with graphite paper coated with hexagonal boron nitride of the same size and then inserted into the through hole of the graphite felt. Then, the electrodes were clamped at both ends of the graphite felt along the length direction and then suspended in the reactor cavity. The reactor was closed and the reactor cavity was first evacuated with a mechanical pump to make the vacuum pressure count value reach 10 Pa. Then, the molecular pump was turned on to continue the evacuation process until the vacuum pressure count value was less than 8×10 - 3 Pa, then slowly introduce argon to normal pressure, turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 82A at a rate of 3A / s, and then keep it for 60s, turn off the power switch and cool it naturally, then take out the obtained clinker, grind it and pass it through a 100-mesh nylon sieve, take the powder under the sieve, and obtain clinker powder (recorded as 7HEC-S1);
[0055] 4) 0.5 g of clinker powder was placed in a mold (the mold cavity was cylindrical with a diameter of 10 mm), and the pressure was slowly increased to 7 MPa, and the pressure was maintained for 2 min to obtain a clinker body (thickness of about 1.5 mm);
[0056] 5) A through hole of about 20 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 100 mm in length, 16 mm in width and 4.75 mm in thickness, and then a graphite paper coated with hexagonal boron nitride was folded in half to form a carrier with a length of 20 mm and a width of 15 mm. The clinker blank was then inserted into the carrier (the upper and lower surfaces of the clinker blank were not completely in contact with the graphite paper), and then inserted into the through hole of the graphite felt. Then, the electrodes were clamped at both ends of the graphite felt along the length direction, and then suspended in the reactor cavity. The reactor was closed, and the reactor cavity was first vacuumed with a mechanical pump to make the vacuum pressure count value reach 10 Pa, and then the molecular pump was turned on to continue the vacuuming process until the vacuum pressure count value was less than 8×10 -3 Pa, and then slowly introduce argon gas to normal pressure, then turn on the power switch to connect the two ends of the graphite felt to AC, then increase the current from 0 to 5A within 7s, and then keep it for 12s, then increase the current to 35A within 7s, and then keep it for 12s, then increase the current to 57A within 7s, and then keep it for 32s, then turn off the power and cool it to room temperature, and then you can get a high entropy carbide ceramic material (seven-element high entropy carbide (Hf 1 / 7 Zr 1 / 7 Ta 1 / 7 Nb 1 / 7Ti 1 / 7 Cr 1 / 7 Mo 1 / 7)C, denoted as 7HEC).
[0057] Performance Test:
[0058] The XRD pattern of the clinker powder in this embodiment is as follows Figure 1 As shown, the XRD pattern of the high entropy carbide ceramic material of this embodiment is as follows Figure 2 shown.
[0059] Depend on Figure 1 It can be seen that the clinker powder 7HEC-S1 in this embodiment contains a high entropy main phase and other solid solution secondary phases.
[0060] Depend on Figure 2 It can be seen that the high entropy carbide ceramic material 7HEC in this embodiment is a pure phase and does not contain other impurity phases.
[0061] After testing (the testing method is the same as that of Example 3), the seven constituent elements Hf, Zr, Ta, Nb, Ti, Cr and Mo in the high entropy carbide ceramic material 7HEC of this embodiment are evenly distributed without obvious segregation, the density of 7HEC is 92.0%, and the hardness value of 7HEC under a load of 0.49N is 26.7GPa.
[0062] Embodiment 3:
[0063] A high entropy carbide ceramic material, the preparation method of which comprises the following steps:
[0064] 1) 0.73 g of HfO2 powder, 0.42 g of ZrO2 powder, 0.76 g of Ta2O5 powder, 0.46 g of Nb2O5 powder, 0.28 g of TiO2 powder, 0.26 g of Cr2O3 powder, 0.50 g of MoO3 powder, 0.31 g of V2O5 powder, 0.80 g of WO3 powder and 1.24 g of carbon powder were added to an agate mortar and manually ground for 60 min to obtain a mixed powder;
[0065] 2) 1.2 g of the mixed powder was placed in a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 10 MPa, and the pressure was maintained for 3 min to obtain a green body (thickness of about 3.5 mm);
[0066] 3) A through hole of about 20 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 100 mm in length, 16 mm in width and 4.75 mm in thickness. Then, the upper and lower surfaces of the green body were covered with graphite paper coated with hexagonal boron nitride of the same size and then inserted into the through hole of the graphite felt. Then, the electrodes were clamped at both ends of the graphite felt along the length direction and then suspended in the reactor cavity. The reactor was closed and the reactor cavity was first evacuated with a mechanical pump to make the vacuum pressure count value reach 10 Pa. Then, the molecular pump was turned on to continue the evacuation process until the vacuum pressure count value was less than 8×10 - 3 Pa, then slowly introduce argon to normal pressure, turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 85A at a rate of 4A / s, and then keep it for 65s, turn off the power switch and cool it naturally, then take out the obtained clinker, grind it and pass it through a 100-mesh nylon sieve, take the powder under the sieve, and obtain clinker powder (recorded as 9HEC-S1);
[0067] 4) 0.5 g of clinker powder was placed in a mold (the mold cavity was cylindrical with a diameter of 10 mm), and the pressure was slowly increased to 8 MPa, and the pressure was maintained for 3 min to obtain a clinker body (about 2 mm thick);
[0068] 5) A through hole of about 20 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 100 mm in length, 16 mm in width and 4.75 mm in thickness, and then a graphite paper coated with hexagonal boron nitride was folded in half to form a carrier with a length of 20 mm and a width of 15 mm. The clinker blank was then inserted into the carrier (the upper and lower surfaces of the clinker blank were not completely in contact with the graphite paper), and then inserted into the through hole of the graphite felt. Then, the electrodes were clamped at both ends of the graphite felt along the length direction, and then suspended in the reactor cavity. The reactor was closed, and the reactor cavity was first vacuumed with a mechanical pump to make the vacuum pressure count value reach 10 Pa, and then the molecular pump was turned on to continue the vacuuming process until the vacuum pressure count value was less than 8×10 -3 Pa, and then slowly introduce argon gas to normal pressure, then turn on the power switch to connect the two ends of the graphite felt to AC, then increase the current from 0 to 6A within 10s, and then keep it for 15s, then increase the current to 40A within 10s, and then keep it for 15s, then increase the current to 60A within 10s, and then keep it for 35s, then turn off the power and cool it to room temperature, and the high entropy carbide ceramic material (nine-element high entropy carbide (Hf 1 / 9 Zr 1 / 9 Ta 1 / 9 Nb 1 / 9Ti 1 / 9 Cr 1 / 9 Mo 1 / 9 V 1 / 9 W1 / 9 )C, denoted as 9HEC).
[0069] Performance Test:
[0070] The XRD pattern of the clinker powder in this embodiment is as follows Figure 1 As shown, the XRD pattern of the high entropy carbide ceramic material of this embodiment is as follows Figure 2 As shown, the scanning electron microscope (SEM) image and EDS element surface distribution map of the high entropy carbide ceramic material of this embodiment are as follows Figure 3 shown.
[0071] Depend on Figure 1 It can be seen that the clinker powder 9HEC-S1 in this embodiment contains a high entropy main phase and other solid solution secondary phases.
[0072] Depend on Figure 2 It can be seen that the high entropy carbide ceramic material 9HEC in this embodiment is a pure phase and does not contain other impurity phases.
[0073] Depend on Figure 3 It can be seen that the nine constituent elements Hf, Zr, Ta, Nb, Ti, Cr, Mo, V and W in the high entropy carbide ceramic material 9HEC of this embodiment are evenly distributed without obvious segregation.
[0074] According to tests, the density of the high entropy carbide ceramic material 9HEC in this embodiment is 94.0%, and the hardness value under a load of 0.49N is 29.6GPa.
[0075] Comparative Example 1:
[0076] A high entropy carbide ceramic material (denoted as 9HEC-1), which is exactly the same as Example 3 except that the graphite paper coated with hexagonal boron nitride in step 5) is replaced with graphite paper and the size of the graphite felt in step 5) is adjusted to 100 mm in length, 18 mm in width and 4.75 mm in thickness during the preparation process.
[0077] Performance Test:
[0078] The XRD pattern of the high entropy carbide ceramic material of this comparative example is as follows Figure 4 shown.
[0079] Depend on Figure 4 It can be seen that what is actually prepared in this comparative example is a multiphase carbide solid solution, not a single-phase high-entropy carbide ceramic material. This may be because the graphite paper (the surface is not coated with hexagonal boron nitride) reacts with the clinker body during the high-temperature heat treatment, resulting in incomplete solid solution of the sample and the presence of residual carbon, or the actual sintering temperature is reduced due to the increase in the size of the graphite felt, resulting in the failure of the solid solution reaction of the clinker body to be completely carried out during the sintering process.
[0080] Comparative Example 2:
[0081] A high entropy carbide ceramic material (denoted as 9HEC-2) is prepared in the same manner as in Example 3 except that the current in step 3) is adjusted from 85 A to 70 A.
[0082] Performance Test:
[0083] The XRD pattern of the high entropy carbide ceramic material of this comparative example is as follows Figure 4 shown.
[0084] Depend on Figure 4 It can be seen that the material prepared in this comparative example is actually a multiphase carbide solid solution, not a single-phase high-entropy carbide ceramic material. This may be because the current selected in step 3) is too small, so that the carbon thermal reduction reaction cannot be completely carried out, resulting in residual oxides in the clinker powder.
[0085] Comparative Example 3:
[0086] A high entropy carbide ceramic material (denoted as 9HEC-3), the preparation method of which comprises the following steps:
[0087] 1) 0.73 g of HfO2 powder, 0.42 g of ZrO2 powder, 0.76 g of Ta2O5 powder, 0.46 g of Nb2O5 powder, 0.28 g of TiO2 powder, 0.26 g of Cr2O3 powder, 0.50 g of MoO3 powder, 0.31 g of V2O5 powder, 0.80 g of WO3 powder and 1.24 g of carbon powder were added to an agate mortar and manually ground for 60 min to obtain a mixed powder;
[0088] 2) 1.2 g of the mixed powder was placed in a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 10 MPa, and the pressure was maintained for 3 min to obtain a green body (thickness of about 3.5 mm);
[0089] 3) A through hole of about 20 mm in length was cut in the middle of the side of a graphite felt (AvCarb, model G475) with a size of 100 mm in length, 16 mm in width and 4.75 mm in thickness. Then, the upper and lower surfaces of the green body were covered with graphite paper coated with hexagonal boron nitride of the same size and then inserted into the through hole of the graphite felt. Then, the electrodes were clamped at both ends of the graphite felt along the length direction and then suspended in the reactor cavity. The reactor was closed and the reactor cavity was first evacuated with a mechanical pump to make the vacuum pressure count value reach 10 Pa. Then, the molecular pump was turned on to continue the evacuation process until the vacuum pressure count value was less than 8×10 - 3Pa, and then slowly introduce argon to normal pressure, then turn on the power switch to connect the two ends of the graphite felt with alternating current, increase the current from 0 to 90A at a rate of 4A / s, and then maintain for 65s, and then turn off the power switch and cool naturally to obtain high entropy carbide ceramic material.
[0090] Performance Test:
[0091] The XRD pattern of the high entropy carbide ceramic material of this comparative example is as follows Figure 4 shown.
[0092] Depend on Figure 4 It can be seen that the single-phase high-entropy carbide ceramic material prepared in this comparative example has a density of only 76.6%, which may be due to the generation of CO gas during the one-step carbon thermal reduction process, which forms a large number of microscopic pore structures inside the material, resulting in a decrease in density.
[0093] Comparative Example 4:
[0094] A high entropy carbide ceramic material (denoted as 9HEC-4) is prepared in the same manner as in Example 3 except that the current in step 5) is adjusted from 60 A to 70 A.
[0095] Performance Test:
[0096] The XRD pattern of the high entropy carbide ceramic material of this comparative example is as follows Figure 4 shown.
[0097] Depend on Figure 4 It can be seen that the material prepared in this comparative example is actually a multiphase carbide solid solution, and the material is obviously deformed. This may be because the current selected in step 5) is too high, resulting in too high a temperature for the prepared sample and phase separation. At the same time, the temperature gradient generated is too large, resulting in material deformation.
[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a high entropy carbide ceramic material, characterized in that: The following steps are involved: 1) mixing and grinding metal oxide powder and carbon powder, wherein the metal oxide powder consists of at least six of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder, to obtain a mixed powder; 2) Pressing the mixed powder into a green body, then covering the upper and lower surfaces of the green body with graphite paper coated with hexagonal boron nitride on the upper surface and embedding graphite felt, then placing it in a protective atmosphere and electrifying the graphite felt to cause a carbon thermal reduction reaction of the green body, then taking out the obtained clinker, grinding and sieving it to obtain clinker powder; 3) The clinker powder is pressed into a clinker body, and then the clinker body is wrapped with graphite paper coated with hexagonal boron nitride and then embedded with graphite felt, and then the graphite felt is electrified in a protective atmosphere to perform electric field sintering on the clinker body, thereby obtaining a high entropy carbide ceramic material; Step 2) The carbon thermal reduction reaction is specifically performed as follows: connecting both ends of the graphite felt to an alternating current, increasing the current from 0 to 80A to 85A at a rate of 2A / s to 4A / s, and then maintaining the current for 55s to 65s; Step 3) The specific operation of the electric field sintering is: connect the two ends of the graphite felt to alternating current, then increase the current from 0 to 4A~6A within 5s~10s, and then maintain for 10s~15s, then increase the current to 30A~40A within 5s~10s, and then maintain for 10s~15s, then increase the current to 55A~60A within 5s~10s, and then maintain for 30s~35s, and then turn off the power for cooling.
2. The preparation method according to claim 1, characterized in that: Step 1): the ratio of the total molar amount of metal atoms in the metal oxide powder to the molar amount of carbon powder is 1:1; Step 1): the metal oxide powder is composed of at least six of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder in equal molar ratios of metal elements; Step 1): the particle sizes of HfO2 powder, ZrO2 powder, TiO2 powder, Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, MoO3 powder, V2O5 powder and WO3 powder are all 1 μm to 3 μm, and the purity is ≥99.9%; Step 1): the particle size of the carbon powder is ≤2 μm, and the purity is ≥99.95%.
3. The preparation method according to claim 1, characterized in that: The pressing in step 2) is carried out under a pressure of 8 MPa to 10 MPa, and the holding time is 1 min to 3 min. The sieve used in step 2) is a nylon sieve with a mesh size of 100.
4. The preparation method according to claim 1 or 3, characterized in that: Step 2) The green body is in the shape of a disc, with a diameter of ≤16 mm and a thickness of ≤3.5 mm; Step 2) The size of the graphite felt is 100 mm to 120 mm in length, 15 mm to 20 mm in width, and 4.75 mm in thickness.
5. The preparation method according to claim 1, characterized in that: Step 3) The pressing is carried out at a pressure of 6 MPa to 8 MPa, and the holding time is 1 min to 3 min.
6. The preparation method according to claim 1 or 5, characterized in that: Step 3) The clinker body is in the shape of a disc, with a diameter of ≤10mm and a thickness of ≤2mm; Step 3) The size of the graphite felt is 100mm-120mm in length, 15mm-20mm in width, and 4.75mm in thickness.
7. A high entropy carbide ceramic material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the high entropy carbide ceramic material as claimed in claim 7 in preparing tool coatings, bearing coatings, bulletproof vest protective layers or tank armored vehicle bulletproof layers.
Citation Information
Patent Citations
High-entropy carbide ceramic powder as well as preparation method and application thereof
CN115286389A